'Tell your own story': manhood, masculinity and racial socialization among black fathers and their sons. Issue 10 (8th August 2016) - Allen, Quaylan
ABSTRACT: This study examines how black fathers and sons in the USA conceptualize manhood and masculinity and the racial socializing practices of black men. Drawing upon data from an ethnography on black male schooling, this paper uses the interviews with fathers and sons to explore how race and gender intersect in how black males make meaning of their gendered performances. Common notions of manhood are articulated, including independence, responsibility and providership. However, race and gender intersect in particular ways for black men. The fathers engaged in particular racial socializing practices preparing their sons for encounters with racism. Both fathers and sons adopted black existentialist perspectives, emphasizing self-determination and resilience as racially and politically motivated acts of resistance. Finally, the paper describes how the fathers modelled to their sons how to navigate racialized spaces as black men.